2015
DOI: 10.1017/s1742170515000435
|View full text |Cite
|
Sign up to set email alerts
|

Increasing corn yield with no-till cropping systems: a case study in South Dakota

Randy L. Anderson

Abstract: No-till practices have improved crop yields in the semiarid Great Plains. However, a recent assessment of research studies across the globe indicated that crop yields are often reduced by no-till. To understand this contrast, we examined corn yields across time in a no-till cropping system of one producer in central South Dakota to identify factors associated with increased yield. The producer started no-till in 1990; by 2013, corn yield increased 116%. In comparison, corn increased only 32% during this interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Our finding that 'reduced crop yield' is regarded as one of the most important barriers for both conservation tillage and cover crops suggests that maximized yield is a common goal among many farmers. Despite potential yield reduction, conservation tillage and cover cropping may benefit farmers through improved economic performance through decreased input costs, such as reduced labor, fuel, nitrogen fertilizer or pesticides requirements (Anderson, 2016;Mahama et al, 2016;Singh et al, 2021). Wang et al (2021b) found that more farmers perceive a profit increase than a yield increase when asked about cover crops and conservation tillage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that 'reduced crop yield' is regarded as one of the most important barriers for both conservation tillage and cover crops suggests that maximized yield is a common goal among many farmers. Despite potential yield reduction, conservation tillage and cover cropping may benefit farmers through improved economic performance through decreased input costs, such as reduced labor, fuel, nitrogen fertilizer or pesticides requirements (Anderson, 2016;Mahama et al, 2016;Singh et al, 2021). Wang et al (2021b) found that more farmers perceive a profit increase than a yield increase when asked about cover crops and conservation tillage.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined farmer perceptions on a number of challenges associated with conservation tillage and cover crops adoption. The primary conservation tillage benefits include input savings (e.g., nitrogen and phosphorus fertilizers) and improved soil health (Reimer et al ., 2012; Anderson, 2016). The majority of farmers faced challenges with conservation tillage practice, including excessive soil moisture, delayed planting of cash crops, reduced cash crop yields and increased dependence on herbicides and fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we assessed impact of no-till on corn ( Zea mays L.) yields across time, comparing a no-till, diverse cropping system [rotation was winter wheat ( Triticum aestivum L.)–dry pea ( Pisum sativum L.)–corn–soybean ( Glycine max (L.) Merr. )–oat ( Avena sativa L.)] to a tilled corn–soybean rotation (Anderson, 2016). In this case study, corn yield increased 116% in no-till across a 25-yr interval, but only 32% in the tilled system.…”
mentioning
confidence: 99%